Development of Writing Skills in Individuals with Learning Difficulties - Miller, Brett; McCardle, Peggy; Connelly, Vince (Studies in Writing, 2017)
This volume highlights writing development and its relation to other cognitive domains, such as language and reading, for individuals who struggle to acquire writing proficiency, including those with specific learning disorders (SLD; e.g., dyslexia, dysgraphia, and specific language impairment) which affect writing skills (e.g., handwriting, composition). Writing and writing development are presented from a transnational perspective with an integrated focus on conceptualizing writing as a developmental process.